EFEKTIVITAS PEMAHAMAN TERHADAP IBU YANG TERINFEKSI HIV DENGAN PERAWATAN KESEHATAN UNTUK MENCEGAH PENULARAN HIV MELALUI IBU PADA ANAK - Aisyah Nur Aini; Agzan Maulana Widjojo; Iftitah Naurah Nur Az Zahro; Denny Oktavina Radianto (KOLONI, 2023)
The number of cases of pregnant women and births with HIV has increased from year to year in the world and in Indonesia. The research problem is how are the experiences of HIV-infected mothers related to family support in childbirth through a qualitative phenomenological view. Survey research method, through the selection of participants using purposive sampling. Data collection uses in-depth interviews and data analysis uses thematic analysis. The results of the study illustrate that some participants received family encouragement in the form of emotional, spiritual, financial, and informational forms, while some others did not receive encouragement. The support obtained by the mother causes a feeling of happiness and serenity. Some of the participants got bad behavior because of the views of their families and health care providers. The conclusion of the study is that nurses participate in nursing care with family involvement focused on the psychological, social and spiritual aspects of the mother up to the gestation period. Keywords: Knowledge, HIV AIDS, Maternal and Child Health.